Respostas
respondido por:
1
x y = 2x - 3 (x;y)
-2 y = 2.(-2) - 3 (-2;-7)
-1 y = 2.(-1) - 3 (-1;-5)
0 y = 2.0 - 3 (0;-3)
1 y = 2.1 - 3 (1;-1)
2 y = 2.2 - 3 (2;1)
3 y = 2.3 - 3 (3;3)
0,5 y = 2.0,5 - 3 (0,5;-2)
-2 y = 2.(-2) - 3 (-2;-7)
-1 y = 2.(-1) - 3 (-1;-5)
0 y = 2.0 - 3 (0;-3)
1 y = 2.1 - 3 (1;-1)
2 y = 2.2 - 3 (2;1)
3 y = 2.3 - 3 (3;3)
0,5 y = 2.0,5 - 3 (0,5;-2)
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás